“Wandering” Advertising Mottos in the Russian Prose of the 1920–30s - Sokolova, Olga (Przegląd Wschodnioeuropejski, 2018)
The article considers the study of such a form of discourses interaction as the metalanguage reflection of one set of discourse markers in another. The analysis is based on the material of advertising and aesthetic discourses (prose of the 1920s–1930s), which involves the tense meta-linguistic reflection of the writers of that time by a new linguistic and communicative situation, as laconically expressed in advertising slogans. To consider this form of discourses interaction, we use a combination of discourse analysis, communicative and linguo-poetic approaches. The article reveals that the metalanguage reflection of advertising slogans allows authors to simulate the situation of actual communication between the addresser (the sender of advertising slogans) and the addressee (the layman – reader of slogans), based on the advertising communicative strategy of deautomatization. The micro-situation of the dialogue violation is projected onto a general sociopolitical picture of a global misunderstanding between the individual and the radically changed surrounding reality.